Comparative Study of Shear Bond Strength of Three Veneering Ceramics to a Zirconia Core - Aalaei Sh; Nematollahi F; Vartanian M; Beyabanaki E (Shiraz University of Medical Sciences, 2016)
Statement of Problem: Fracture of veneering porcelain has been described as the most frequent reason for the failure of zirconia-based fixed restorations. Objectives: The purpose of this study was to evaluate and compare the shear bond strength of a zirconium oxide core material to three commercial veneering ceramics. Materials and Methods: Three types of veneering ceramics were selected including IPS -emax Ceram, Vita VM9, and Cerabien. Thirty block specimens of zirconia core material were prepared in 4×4×9 mm dimensions. Three groups were created and the veneering ceramic was added to each of 10 blocks. Shear bond test was conducted with universal testing machine. Data were analyzed using one-way ANOVA (p = 0.05). Results: Mean shear bond strength values and standard deviations were 26.03 MPa (6.32), 23.85 MPa (4.01), and 19.16 MPa (3.72) for Vita VM9, IPS emax Ceram, and Cerabien, respectively. Cerabien ceramic showed more failure as compared to the other ceramics. However, there was no significant difference among the three veneering groups. Conclusions: Within the limitation of this study, it can be concluded that shear bond strength between zirconia core and three veneering ceramics was not significantly different.